Metrology, Inspection, and Process Control for Microlithography XVIII 2004
DOI: 10.1117/12.532896
|View full text |Cite
|
Sign up to set email alerts
|

Segmented alignment mark optimization and signal strength enhancement for deep trench process

Abstract: This study characterizes the process influence on the alignment signal of deep trench (DT) process, and correlates product overlay with alignment results based on volume production data. The affecting processes include various steps of polysilicon thickness, nitride and oxide films, recess etch depth control, and resist thickness impact. Correlation also proves that the alignment signal plays an important role at the resulted long-term overlay stability. In order to improve the signal strength, further study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…It is noted here that the scaling of alignment pitch and process segmentation requirements is not only limited to BEOL processes. Similar trends are observed in FEOL processes like the deep trench capacitor process [10,11,12], and metal-gate shallow trench isolation. Effectively the scatter bars presented in this paper could be used as marks in the FEOL processing.…”
Section: Future Worksupporting
confidence: 72%
“…It is noted here that the scaling of alignment pitch and process segmentation requirements is not only limited to BEOL processes. Similar trends are observed in FEOL processes like the deep trench capacitor process [10,11,12], and metal-gate shallow trench isolation. Effectively the scatter bars presented in this paper could be used as marks in the FEOL processing.…”
Section: Future Worksupporting
confidence: 72%
“…Figure-01 shows the mark cell size of alignment marks for the phase grating alignment sensor. It was already reported that higher diffraction order mark design was more robust using the conventional ASML mark family on various process layers [1][2][3][4][5][6]. Using new SMASH marks, however, it has not reported which diffraction order has higher robustness on our process layers, thus, it is very motive to investigate which diffraction order marks to detect for alignment with new SMASH marks on our process layers from the view point of high robustness.…”
Section: Fundamental and Mark Typesmentioning
confidence: 88%
“…Such pure high order AA gratings lead to more alignment signal than the AH gratings, therefore such design has a significant advantage in color resist applications. Refer to [2] and [3] for earlier usage. …”
Section: Pure High Order Markmentioning
confidence: 99%